Performance Evaluation of Encrypted Text Message Transmission in 5G Compatible Orthogonal Multi-level Chaos Shift Keying Modulation Scheme Aided MIMO Wireless Communication System (Global Journal of Computer Science and Technology, 2018)
- In this paper, a comprehensive performance evaluative study has been made on encrypted text message transmission in 5G compatible orthogonal multi-level chaos shift keying modulation scheme aided MIMO wireless communication system. The 4 X 4 multi-antenna supported simulated system incorporates four channel coding (1/2-rated Convolutional, (3, 2) SPC, LDP Cand Repeat and Accumulate (RA)), different signal detection (MMSE, ZF, Cholesky decomposition and Group Detection (GD) approach aided Efficient ZeroForcing (ZF)), and Chaotic Walsh-Hadamard encoding schemes.
Keywords: OM-DCSK modulation; scambing; Hilbert transform and walsh-hadamard codes; signal to noise ratio (SNR)